2014
DOI: 10.1007/s00464-014-3961-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of conservative percutaneous cholecystostomy in high-risk patients with acute cholecystitis and risk factors leading to surgery

Abstract: PC is a safe and effective therapeutic option in high-risk patients with acute cholecystitis, or for preoperative management. The decisive risk factors for surgery after PC were age, ASA score, and CVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 16 publications
2
41
0
3
Order By: Relevance
“…Many prior studies demonstrate that cholecystostomy tube placement is a safe alternative to cholecystectomy for patients with acute gallbladder disease, but primarily report this intervention as “safe” and “feasible.” 46,8,10,11,1519 Yet, simply reporting feasibility of an intervention does not translate to overall outcomes in these patients and still may have severe consequences including mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies demonstrate that cholecystostomy tube placement is a safe alternative to cholecystectomy for patients with acute gallbladder disease, but primarily report this intervention as “safe” and “feasible.” 46,8,10,11,1519 Yet, simply reporting feasibility of an intervention does not translate to overall outcomes in these patients and still may have severe consequences including mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Pri teh bolnikih se poleg podpornega zdravljenja priporoča urgentna holecistektomija pri biliarnem peritonitisu po perforaciji žolčnika. Če je pri bolniku operacija zelo tvegana, se lahko napravi perkutano dreniranje žolčnika oziroma perkutana holecistostoma ter kasneje odložena holecistektomija, ko je bolnik stabilen in v izboljšanem stanju (24).…”
Section: Kirurško Zdravljenjeunclassified
“…Gre za minimalno invaziven poseg, ki ga opravi interventni radiolog pod nadzorom UZ (24). Svetuje se pristop skozi jetra, torej dreniranje žolčnika skozi jetrni parenhim zaradi manjše možnosti iztekanja vsebine žolč-nika v trebušno votlino in nevarnosti za biliarni peritonitis (24).…”
Section: Perkutano Dreniranje žOlčnika -Perkutana Holecistostomaunclassified
See 1 more Smart Citation
“…These older patients generally have comorbidities, which increases the risk of perioperative complications associated with cholecystectomy [2][3][4]. Thus, several studies have indicated the clinical benefits of non-surgical measures such as percutaneous transhepatic gallbladder aspiration (PTGBA) and percutaneous transhepatic gallbladder drainage (PTGBD) as treatment options for acute cholecystitis [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%